2018
DOI: 10.1063/1.5053844
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of quasi-type-II structure in GaAs/GaAsSb/GaAs coaxial single quantum-well nanowires

Abstract: The GaAsSb-based quantum well plays a very important role in optoelectronic devices due to its excellent wavelength tunability. When the dimension reduces, the quantum confinement effect will take place and the quantum well in nanowires will show many interesting characteristics. GaAsSbbased quantum-well nanowires are of contemporary interest. However, the properties of the quasitype-II structure in a single quantum well nanowire have been rarely investigated. Here, we grow GaAs/GaAs 0.92 Sb 0.08 /GaAs coaxial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 116 publications
(35 citation statements)
references
References 25 publications
0
35
0
Order By: Relevance
“…As the temperature increases to about 50 • C, the structure of HIPs takes a tetragonal phase with the space group P4/mbm, and at temperatures above 300 • C, they are in the original Coatings 2021, 11, 1173 2 of 13 cubic phase with the space group Pm3m. In hybrid perovskite structures, by changing the halogens from iodine to bromine and then chlorine, the BX 6 octahedral volume decreases, resulting in a reduction in total volume of the structures [85][86][87][88][89][90].To acquire a comprehensive knowledge of the electrical and optical properties of semiconductor compounds, the band structure, electron density, charge carrier mobility, density of states, and dielectric function must be investigated [91][92][93][94][95].…”
Section: Introductionmentioning
confidence: 99%
“…As the temperature increases to about 50 • C, the structure of HIPs takes a tetragonal phase with the space group P4/mbm, and at temperatures above 300 • C, they are in the original Coatings 2021, 11, 1173 2 of 13 cubic phase with the space group Pm3m. In hybrid perovskite structures, by changing the halogens from iodine to bromine and then chlorine, the BX 6 octahedral volume decreases, resulting in a reduction in total volume of the structures [85][86][87][88][89][90].To acquire a comprehensive knowledge of the electrical and optical properties of semiconductor compounds, the band structure, electron density, charge carrier mobility, density of states, and dielectric function must be investigated [91][92][93][94][95].…”
Section: Introductionmentioning
confidence: 99%
“…In quasi-type-II band alignment, there are two recombination channels for excitons at the same time, one is the recombination between the photoexcited electrons and holes are localized in the well material (type-I like recombination), and the other is the recombination between the photoexcited electron and hole are localized in two different semiconductors (type-II like recombination). The band structure of GaAs 1Àx Sb x in the quantum well can be described by the empirical model proposed by Teissier et al 13,16 As it is shown in Fig. 2(d), the conduction bandgap offset in sample A and sample B is $20 meV and $28 meV, respectively.…”
Section: Resultsmentioning
confidence: 90%
“…Specic growth parameters can be referred to our previous publication. 13,14 The Sb component in the GaAs 1Àx Sb x layer can be wellcontrolled by adjusting the beam ratio of the As and Sb uxs. For sample A, the beam equivalent pressure of As was set to 2.1 la10 À6 torr and the Sb ux was set to 1.9 s 10 À7 torr.…”
Section: Methodsmentioning
confidence: 99%
“…The bandgap of the material is changed because of the discretization of the electron energy, which can be controlled by the nanometers size particles. The nanostructured glasses especially nano-chalcogenides show a dramatic change in their optical and electronic properties on reduction of size below the excitonic size [95,96]. Depending on the deposition technique used, the micro/nanostructure of thin films can be more or less complex.…”
Section: Optical Propertiesmentioning
confidence: 99%